Optically Anisotropic Thin Films by Shear‐Oriented Assembly of Colloidal Nanorods. (13th May 2013) - Kim, Jongwook; Peretti, Jacques; Lahlil, Khalid; Boilot, Jean‐Pierre; Gacoin, Thierry
<x xml:space="preserve">Abstract</x> Device‐scale thin films of highly oriented (in‐plane) colloidal nanorods are made available by using a simple coating process involving thixotropic rod gel suspensions. Application of this process to LaPO4 nanorods leads to films exhibiting outstanding anisotropic optical properties, such as a remarkably large birefringence (Δn = 0.13) associated with high transparency, and sharply polarized fluorescence spectra when doped with europium. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>